WHAT IS SOCIAL ABOUT SOCIAL MEDIA? The Rejuvenation of Television as social media - Aganbi, Victor (IJRDO - Journal of Business Management, 2021)
WHAT IS SOCIAL ABOUT SOCIAL MEDIA: The Rejuvenation of Television as Social Media highlights television as the dominant social medium of all time. Communication of any sort is already social interaction involving the sending of a message to a receiver, and the feelings and thoughts of the receiver upon interpreting the message within the viewpoint of a single linear model or two linear models stacked on top of each other to cater for feedback loop in the S-M-M-R (Sender-Message-Medium-Receiver) communication framework. "Truth" and "ideas" are constructed or invented through the social process wherein the sender channels a message to the receiver and the receiver then becomes the sender and channels a message to the original sender. This feedback model includes cultural background, ethnicity, geographic location, extent of travel, and general personal experiences accumulated over the course of interactant’s lifetime. Thus, the question “what is social about social media” is rhetorical and points to the obvious – the human elements (sender and receiver) define any communication process as SOCIAL and any communication media as SOCIAL MEDIA. Though instantaneity of message delivery and simultaneousness of feedback are contingent to mass communication, they remain elusive and constitute the problem inherent in nearly all forms of media, including the so-called social media platforms. However, social media and television broadcasting have a number of connections and interrelationships that have led to the phenomenon of Social Television. Social Television is an emerging communication digital technology centered around real-time interactivity involving media displayed on television. Through in-depth review, analyses and synthesis of scanty literature, this research questions the description of television as “traditional” or “old.” And, more so, the worn phrase “social media” or “emergent media” in exclusion of television is misnomer. Television – the underrated, overlooked but potentially the most powerful social medium from its humble beginnings, can be more appropriately celebrated as rejuvenated social media. In conclusion, this researcher proposes an updated definition and categorisation of television as social media. The author further makes the case that as television has always been social, never ceased to evolve and is still evolving as social media, it qualifies as emergent media consistent with its dramatically expanding capacity and capabilities beyond sound, picture and text.